Validity and reliability of the A-test in assessing the functional capacity of patients with heart failure - Ilić, Dejan; Tomić, Dragana; Djurdjević, Jovana; Obradović, Slobodan (Vojnosanitetski pregled, 2025)
Background/Aim. Before initiating early rehabilitation, it is essential to assess the functional status of patients with heart failure (HF). Although the Barthel Index (BI) is well-established, the A-test, originally developed for traumatology and orthopedic patients, has recently been introduced into broader clinical practice. The aim of this study was to evaluate the validity and reliability of the A-test in assessing functional status in patients with HF. Methods. The study included patients of both sexes with HF, regardless of age or left ventricular ejection fraction, classified according to the New York Heart Association (NYHA) I–IV class, with Mini-Mental State Examination (MMSE) scores ≥ 24, who were tested daily at the same time. Two experienced senior physiotherapists performed the testing, and they completed the A-test and BI separately. Results. A total of 77 patients were enrolled, two-thirds of whom were male, with a mean age of 72 years and a mean ejection fraction of 41.83% [standard deviation (SD) = 11.46]. The average NYHA class at admission, 2.75 (SD = 1.05), and discharge, 2.42 (SD = 1.12), showed a statistically significant improvement (Z = -4.914, p
Keywords: heart failure; physical therapy; predictive value of tests; rehabilitation.